Development and testing of a new electronic foot health promotion programme on nurses’ foot self-care - Stolt, Minna (BMC Nurs, 2020)
BACKGROUND: Nurses form the largest professional group in health care, and they spend most of their working day on their feet. From the perspective of work well-being, healthy feet are important to tolerate the physical demands of nursing work. However, little is known about how nurses’ foot self-care practices can be promoted with computerised interventions. The aim of this study was two-fold: to explore the preliminary effects of the electronic Foot Health Promotion Programme (FHPP) on foot self-care in nurses and to examine the usability of the programme. METHODS: A single group pretest-posttest design was used. The FHPP was targeted at nurses working in the operating theatre. The FHPP lasted for 4 weeks and focused on improving nurses’ knowledge and awareness of foot self-care through self-directed learning tasks. The primary outcome was knowledge of foot self-care. The secondary outcomes were foot health and work ability. Thirty-seven participants completed the study. The outcomes were assessed at baseline (April–June 2017) and 4 weeks (August–September 2017) after the intervention ended. The data were analysed statistically. RESULTS: Participants’ knowledge of foot self-care and foot health improved; however, the changes were not statistically significant. The FHPP was considered to be usable and has potential as a tool to increase knowledge of foot self-care among nurses. CONCLUSIONS: The FHPP developed in this study is a newly developed potential tool to increase nurses’ knowledge of foot self-care. Application of the FHPP as part of occupational health care may enhance nursing personnel’s foot self-care and lower extremity health. TRIAL REGISTRATION: ClinicalTrials.gov NCT03116451, 17.4.2017.